PERANCANGAN SISTEM INFORMASI PENJUALAN HANDPHONE BERBASIS WEB PADA TOKO SERIES PONSEL - Manorang Gultom; Kristina Kristina; Jordan Jordan (LPPM Universitas Widya Dharma Pontianak, 2023)
Along with the development of time, a lot of technology has become increasingly sophisticated and is present to help human work, especially in the modern era like today, computers and cellphones are indispensable to support every activity carried out by humans in all fields ranging from education to education. in daily work. The perceived benefits of using computer technology are being able to process large amounts of data, archiving data or documents and being able to generate reports automatically from data that has been previously processed on a computer. Sales is an activity carried out individually or in groups that offer goods or services that can be purchased by customers. Mobile Phone Series Store is a store that sells various types of cellphones, ranging from the cheapest to the most expensive prices, besides that this store also sells credit, vouchers and other cellphone accessories. From the background of this research the author will analyze the sales process at the Cellphone Series Store and build a web-based sales information system. The author uses a system design analysis technique that uses the Unified Modeling Language (UML) modeling. The system design application used is Sublime Text Editor, Xampp, MySql. The results of this study in the form of a Web-based sales information system at the Cellphone Series Store which aims to assist data processing of goods, sales and purchases and facilitate the manufacture of computerized and sales reports. From this research, it can be concluded that the system is made using web-based computer technology that can be accessed easily while making it easier for owners to record sales transactions by implementing the idea of ​​a Web-Based Sales Information System. The existence of a web-based sales information system at the Mobile Series Store makes it easier for business owners to carry out promotions with a wider range. The author also evaluates the system on an ongoing basis to avoid any errors or errors that will affect system performance. Keywords: Designing, System, Information, Sales, Web